2010
DOI: 10.1590/s1516-31802010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common thrombophilia markers and risk factors in Indian patients with primary venous thrombosis

Abstract: CONTEXT AND OBJECTIVE: Venous thrombosis occurs as a result of interaction of genetic and acquired factors including activated protein C resistance (APC-R), fibrinogen levels, antithrombin, protein C, protein S, lupus anticoagulants and anticardiolipin antibodies. This study was aimed at determining the prevalence of these common thrombophilia markers in Asian Indians with primary venous thrombosis. DESIGN AND SETTING: This was a cross-sectional study carried out in Mumbai. METHODS: Samples from 78 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
(31 reference statements)
2
17
2
Order By: Relevance
“…AT estimation was done on a biochemistry analyzer, as mentioned in a previous study on venous thrombosis. 7 The diagnostic methods for detecting MI were troponin T, CK MB and aminotransferase; EKG or echocardiography during acute phase of MI followed by coronary angiography; radionuclide lung scanning or angiography for pulmonary embolism; arteriography for peripheral arterial occlusions; and CT scan, magnetic resonance imaging or arteriography for cerebral thrombosis. For a diagnosis of transient ischemic attack (TIA), a focal neurological deficit resolving within 24 hours was required, whereas if it persisted beyond 24 hours, a diagnosis of stroke was made.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…AT estimation was done on a biochemistry analyzer, as mentioned in a previous study on venous thrombosis. 7 The diagnostic methods for detecting MI were troponin T, CK MB and aminotransferase; EKG or echocardiography during acute phase of MI followed by coronary angiography; radionuclide lung scanning or angiography for pulmonary embolism; arteriography for peripheral arterial occlusions; and CT scan, magnetic resonance imaging or arteriography for cerebral thrombosis. For a diagnosis of transient ischemic attack (TIA), a focal neurological deficit resolving within 24 hours was required, whereas if it persisted beyond 24 hours, a diagnosis of stroke was made.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…In a study conducted by Mishra et al a similar average age for first thrombotic event was found to be 36 years. 4 An association was found between low levels of protein C or S or resistance to factor V and the thrombotic event.…”
Section: Discussionmentioning
confidence: 99%
“…It is this hypercoaguable condition that paves way to thrombotic events more often in pregnant population than in general population resulting in adverse outcomes like abortions or recurrent abortions, intraurine growth restriction, intrauterine fetal demise, placental abruption and preeclampsia. [1][2][3][4][5][6][7][8][9][10][11][12][13] Hence, the evaluation and management of thrombophilia is imperative in women who have history of fetal loss/losses or adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The thrombotic events are not only restricted to venous thromboembolism but also can cause fetal loss (abortions or recurrent abortions and fetal demise), placental abruption, intrauterine growth restriction and severe preeclampsia. [1][2][3][4][5][6][7][8][9][10][11][12][13] In the recent years various studies have evaluated the role of administering thromboprophylaxis to patients with previous history of adverse obstetric outcomes who have tested positive for inherited and acquired thrombophilia. 11,[14][15][16][17] This study adds to the existing data base discerning the role of thromboprophylaxis with heparin and ecosprin in patients with thrombophilia in pregnancy.…”
Section: Introductionmentioning
confidence: 99%